Emerging toxicity of 5,6-methylenedioxy-2-aminoindane (MDAI): Pharmacokinetics, behaviour, thermoregulation and LD50 in rats - Páleníček, Tomáš; Lhotková, Eva; Žídková, Monika; Balíková, Marie; Kuchař, Martin; Himl, Michal; Mikšátková, Petra; Čegan, Martin; Valeš, Karel; Tylš, Filip; Horsley, Rachel R (Progress in neuro-psychopharmacology & biological psychiatry, 2016)
MDAI (5,6-Methylenedioxy-2-aminoindane) has a reputation as a non-neurotoxic ecstasy replacement amongst recreational users, however the drug has been implicated in some severe and lethal intoxications. Due to this, and the fact that the drug is almost unexplored scientifically we investigated a broad range of effects of acute MDAI administration: pharmacokinetics (in sera, brain, liver and lung); behaviour (open field; prepulse inhibition, PPI); acute effects on thermoregulation (in group-/individually-housed rats); and systemic toxicity (median lethal dose, LD50) in Wistar rats. Pharmacokinetics of MDAI was rapid, maximum median concentration in serum and brain was attained 30min and almost returned to zero 6h after subcutaneous (sc.) administration of 10mg/kg MDAI; brain/serum ratio was ~4. MDAI particularly accumulated in lung tissue. In the open field, MDAI (5, 10, 20 and 40mg/kg sc.) increased exploratory activity, induced signs of behavioural serotonin syndrome and reduced locomotor habituation, although by 60min some effects had diminished. All doses of MDAI significantly disrupted PPI and the effect was present during the onset of its action as well as 60min after treatment. Unexpectedly, 40mg/kg MDAI killed 90% of animals in the first behavioural test, hence LD50 tests were conducted which yielded 28.33mg/kg sc. and 35mg/kg intravenous but was not established up to 40mg/kg after gastric administration. Disseminated intravascular coagulopathy (DIC) with brain oedema was concluded as a direct cause of death in sc. treated animals. Finally, MDAI (10, 20mg/kg sc.) caused hyperthermia and perspiration in group-housed rats. In conclusion, the drug had fast pharmacokinetics and accumulated in lipohilic tissues. Behavioural findings were consistent with mild, transient stimulation with anxiolysis and disruption of sensorimotor processing. Together with hyperthermia, the drug had a similar profile to related entactogens, especially 3,4-metyhlenedioxymethamphetamine (MDMA, ecstasy) and paramethoxymethamphetamine (PMMA). Surprisingly subcutaneous MDAI appears to be more lethal than previously thought and its serotonergic toxicity is likely exacerbated by group housing conditions. MDAI therefore poses greater risks to physical and mental health than recognised hitherto.
Keywords: Body Temperature Regulation; termoregulace; Serotonin Syndrome; psychotropní léky; Wistar rat; Prepulse inhibition; Habituation, Psychophysiologic; indany; Lethal Dose 50; Brain; habituace (psychofyziologie); Sensory gating; zvířata; Open field; Psychotropic Drugs; Saliva; Prepulse Inhibition; Myocardium; mozek; mužské pohlaví; Male; Pharmacokinetics; Animals; Motor Activity; Sweating; Body temperature; serotoninový syndrom; Locomotion; Median lethal dose; pocení; sliny; Rats, Wistar; prepulsní inhibice; LD50; srdce; Toxicology; myokard; Heart; MDAI; potkani Wistar; pohybová aktivita; 5,6-methylenedioxy-2-aminoindane; Indans